Diagnosa Dampak Penggunaan Softlens Menggunakan Certainty Factor BerbasisAndroid - Vivi Yohana Zebua (Interaksi : Jurnal Informatika Dan Teknologi Sistem Informasi, 2025)
An expert system (Expert System) was first developed by the Artificial Intelligence (AI) community in the mid-1960s. The expert system that first appeared was the General-purpose Problem Solver (GPS) developed by Newel and Simon (Turban, l995). An expert system is a computer program that simulates the judgment and behavior of humans or organizations that have expert knowledge and experience in a particular field. Usually systems like this contain a knowledge base containing accumulated experience and a set of rules for applying basic knowledge to each specific situation. In the world of technology, especially technology that operates in the field of communication, such as cellular communication technology, has created major changes. The rapid development of this technological device has given rise to a variety of new functions apart from its main function as a communication tool. Today's mobile phones are supported by the Android operating system, where Android is a Linux-based mobile phone operating system. Android is the latest breakthrough platform for mobile devices which is very popular with mobile device users, this is because the system performance on Android is easy to operate with an attractive appearance and can be